Serum vasohibin‐1 levels: A potential marker of dermal and pulmonary fibrosis in systemic sclerosis. Issue 7 (16th March 2021) - Fukui, Yuki; Nakamura, Kouki; Hirabayashi, Megumi; Miyagawa, Takuya; Toyama, Satoshi; Omatsu, Jun; Awaji, Kentaro; Ikawa, Tetsuya; Norimatsu, Yuta; Yoshizaki, Ayumi; Sato, Shinichi; Asano, Yoshihide
Abstract: Vasohibin‐1 (VASH‐1) is a potent anti‐angiogenic factor mainly produced by endothelial cells. In addition, VASH‐1 prevents TGF‐β–dependent activation of renal fibroblasts. Since systemic sclerosis (SSc) is an autoimmune disease characterized by vasculopathy and fibrosis of multiple organs, VASH‐1 may be involved in the development of this disease. In this study, we investigated the potential role of VASH‐1 in SSc by evaluating the clinical correlation between serum VASH‐1 levels and the expression of VASH‐1 in SSc‐involved skin. Serum VASH‐1 levels were higher in SSc patients, especially those with diffuse cutaneous involvement, than in healthy controls and positively correlated with skin score. Furthermore, SSc patients with interstitial lung disease had significantly elevated levels of serum VASH‐1 as compared to those without. Importantly, serum VASH‐1 levels correlated inversely with both the percentage of predicted vital capacity and the percentage of predicted diffusion lung capacity for carbon monoxide and positively with serum KL‐6 levels, but not serum surfactant protein D levels. In SSc‐involved skin, VASH1 mRNA was remarkably upregulated compared with healthy control skin, but the major source of VASH‐1 was not clear. Fli1 deficiency, a predisposing factor inducing SSc‐like endothelial properties, did not affect VASH‐1 expression in human dermal microvascular endothelial cells. Collectively, these results suggest that VASH‐1 upregulation in the skin and sera is linked to dermal and pulmonary fibrotic changes in SSc, while the contribution of VASH‐1 to SSc vasculopathy seems to be limited.